Socio-cultural perceptions of indoor air pollution among rural migrant households in Ado Ekiti, Nigeria - Akintan, Oluwakemi Bolanle (2014)
Many households in developing countries rely on biomass (wood, charcoal, agricultural wastes, sawdust, and animal dung) and coal to meet their energy needs. The burning of these fuels in open fires creates environmental problems one of which is indoor air pollution (IAP). For effective reduction of indoor air pollution in sub-Saharan Africa, it is therefore, important to understand factors that determine the choice and uptake of cleaner fuels for household energy use. This research investigates the salient factors influencing households in developing countries in choosing fuel types, using the households in peri-urban areas of Ado Ekiti, Ekiti State, Nigeria as a case study.